Hybrid-Neuro Bandit: A Bandit Model for Online Recommendation - Bansal, Nipun; Bala, Manju; Sharma, Kapil (Defence Science Journal, 2024)
Contextual multi-arm Bandit (CMAB) is a popular framework for sequential decision-making problems where an agent must repeatedly choose among multiple actions, each with an unknown reward distribution..................